IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PENDIDIKAN KARAKTER PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SDN 22 SULUR MEDAN TAHUN PELAJARAN 2023/2024 - Nurul Hidayat; Arnadi Arnadi; Hadisa Putri (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim of this research is to reveal about: 1). Teacher Preparation in Implementing the Independent Curriculum for Character Education in Pancasila Education Subjects at SDN 22 Sulur Medan for the 2023/2024 Academic Year? 2). Are Teachers Implementing Independent Curriculum Steps Able to Improve Character in Pancasila Education Subjects at SDN 22 Sulur Medan for the 2023/2024 Academic Year? This research uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that: 1. Teacher preparation in implementing the Independent Curriculum for Character Education in Pancasila Education Subjects at SDN 22 Sulur Medan for the 2023/2024 academic year, namely teachers preparing to implement the Independent Curriculum for Pancasila Education by preparing inclusive and adaptive lesson plans, using quality references, and developing materials teaching that includes character values. The school principal's support and use of varied learning media create an effective and relevant learning environment. 2. Teachers Implementing the Independent Curriculum Steps to Improve Character in Pancasila Education Subjects at SDN 22 Sulur Medan for the 2023/2024 Academic Year, namely, the implementation of the Independent Curriculum improves student character through student-centered learning methodologies, such as group discussions, project-based learning, and inquiry methods. A variety of learning media, both modern and traditional technology, makes the learning atmosphere more interesting. Comprehensive evaluation with effective feedback, observation, portfolio, and reflection helps teachers understand student progress and create an inclusive learning environment, support positive character development, and achieve effective, relevant, and holistic learning.